Beta-blocker Therapy is Associated with Decreased 1-year Mortality After Emergency Laparotomy in Geriatric Patients. (March 2021) - Maghami, S.; Cao, Y.; Ahl, R.; Detlofsson, E.; Matthiessen, P.; Sarani, B.; Mohseni, S.
Background and Aims: Emergency laparotomy is associated with a great risk of mortality in the elderly. The hyperadrenergic state induced by surgical trauma may play an important role in the pathophysiology of this increased risk. Studies have shown that beta-blocker exposure may be associated with decreased morbidity and mortality in the perioperative period. We aimed to study the effect of beta-blocker on mortality in geriatric patients undergoing emergency laparotomy. Material and Methods: This is a retrospective study of patients who underwent emergency laparotomy between 1 January 2015 and 31 December 2016 at a single institution. The outcomes of interest were the association between post-operative complications and in-hospital and 1-year mortality in patients on beta-blocker therapy (BB (+) ) and those who were not (BB (−) ). The Poisson regression analysis was used to evaluate the association. Results: A total of 192 patients were included of whom 62 (32.2%) had pre-operative beta-blocker therapy with continued exposure during their hospital stay. The in-hospital mortality was 17.7% in the BB (+) and 23.8% in the BB (−) cohorts ( p  = 0.441). One-year mortality was significantly lower in the BB (+) group compared to the BB (−) group (30.6% versus 47.7%; p  = 0.038). After adjusting for confounders, the incidence of deaths during 1 year post-operatively decreased by 35% in the BB (+) group (incidence rate ratio = 0.65, p  = 0.004). No significant differences in the incidence of post-operative complications between the two groups could be measured. Conclusion: Beta-blocker therapy may be associated with reduced 1-year mortality following emergency laparotomy in geriatric patients.